Saline irrigation for allergic rhinitis - Head, Karen; Snidvongs, Kornkiat; Glew, Simon; Scadding, Glenis; Schilder, Anne Gm; Philpott, Carl; Hopkins, Claire (Cochrane database of systematic reviews, 2018)
Allergic rhinitis is a common condition affecting both adults and children. Patients experience symptoms of nasal obstruction, rhinorrhoea, sneezing and nasal itching, which may affect their quality of life.Nasal irrigation with saline (salty water), also known as nasal douching, washing or lavage, is a procedure that rinses the nasal cavity with isotonic or hypertonic saline solutions. It can be performed with low positive pressure from a spray, pump or squirt bottle, with a nebuliser or with gravity-based pressure in which the person instils saline into one nostril and allows it to drain out of the other. Saline solutions are available over the counter and can be used alone or as an adjunct to other therapies. To evaluate the effects of nasal saline irrigation in people with allergic rhinitis. The Cochrane ENT Information Specialist searched the ENT Trials Register; CENTRAL; Ovid MEDLINE; Ovid Embase; CINAHL; Web of Science; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 23 November 2017. Randomised controlled trials (RCTs) comparing nasal saline irrigation, delivered by any means and with any volume, tonicity and alkalinity, with (a) no nasal saline irrigation or (b) other pharmacological treatments in adults and children with allergic rhinitis. We included studies comparing nasal saline versus no saline, where all participants also received pharmacological treatment (intranasal corticosteroids or oral antihistamines). We used the standard methodological procedures expected by Cochrane. Primary outcomes were patient-reported disease severity and a common adverse effect - epistaxis. Secondary outcomes were disease-specific health-related quality of life (HRQL), individual symptom scores, general HRQL, the adverse effects of local irritation or discomfort, ear symptoms (pain or pressure) and nasal endoscopy scores. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. We included 14 studies (747 participants). The studies included children (seven studies, 499 participants) and adults (seven studies, 248 participants). No studies reported outcomes beyond three months follow-up. Saline volumes ranged from 'very low' to 'high' volume. Where stated, studies used either hypertonic or isotonic saline solution.Nasal saline versus no saline treatmentAll seven studies (112 adults; 332 children) evaluating this comparison used different scoring systems for patient-reported disease severity, so we pooled the data using the standardised mean difference (SMD). Saline irrigation may improve patient-reported disease severity compared with no saline at up to four weeks (SMD -1.32, 95% confidence interval (CI) -1.84 to -0.81; 407 participants; 6 studies; low quality) and between four weeks and three months (SMD -1.44, 95% CI -2.39 to -0.48; 167 participants; 5 studies; low quality). Although the evidence was low quality the SMD values at both time points are considered large effect sizes. Subgroup analysis showed the improvement in both adults and children. Subgroup analyses for volume and tonicity were inconclusive due to heterogeneity.Two studies reported methods for recording adverse effects and five studies mentioned them. Two studies (240 children) reported no adverse effects (epistaxis or local discomfort) in either group and three only reported no adverse effects in the saline group.One study (48 children) reported disease-specific HRQL using a modified RCQ-36 scale. It was uncertain whether there was a difference between the groups at any of the specified time points (very low quality). No other secondary outcomes were reported.Nasal saline versus no saline with adjuvant use of intranasal steroids or oral antihistamines Three studies (40 adults; 79 children) compared saline with intranasal steroids versus intranasal steroids alone; one study (14 adults) compared saline with oral antihistamines versus oral antihistamines alone. It is uncertain if there is a difference in patient-reported disease severity at up to four weeks (SMD -0.60, 95% CI -1.34 to 0.15; 32 participants; 2 studies; very low quality) or from four weeks to three months (SMD -0.32, 95% CI -0.85 to 0.21; 58 participants; 2 studies; very low quality). Although none of the studies reported methods for recording adverse effects, three mentioned them: one study (40 adults; adjuvant intranasal steroids) reported no adverse effects (epistaxis or local discomfort) in either group; the other two only reported no adverse effects in the saline group.It is uncertain if saline irrigation in addition to pharmacological treatment improved disease-specific HRQL at four weeks to three months, compared with pharmacological treatment alone (SMD -1.26, 95% CI -2.47 to -0.05; 54 participants; 2 studies; very low quality). No other secondary outcomes were reported.Nasal saline versus intranasal steroidsIt is uncertain if there was a difference in patient-reported disease severity between nasal saline and intranasal steroids at up to four weeks (MD 1.06, 95% CI -1.65 to 3.77; 14 participants; 1 study), or between four weeks and three months (SMD 1.26, 95% CI -0.92 to 3.43; 97 participants; 3 studies), or indisease-specific HRQL between four weeks and three months (SMD 0.01, 95% CI -0.73 to 0.75; 83 participants; 2 studies). Only one study reported methods for recording adverse effects although three studies mentioned them. One (21 participants) reported two withdrawals due to adverse effects but did not describe these or state which group. Three studies reported no adverse effects (epistaxis or local discomfort) with saline, although one study reported that 27% of participants experienced local discomfort with steroid use. No other secondary outcomes were reported. Saline irrigation may reduce patient-reported disease severity compared with no saline irrigation at up to three months in both adults and children with allergic rhinitis, with no reported adverse effects. No data were available for any outcomes beyond three months. The overall quality of evidence was low or very low. The included studies were generally small and used a range of different outcome measures to report disease severity scores, with unclear validation. This review did not include direct comparisons of saline types (e.g. different volume, tonicity).Since saline irrigation could provide a cheap, safe and acceptable alternative to intranasal steroids and antihistamines further high-quality, adequately powered research in this area is warranted.